2021
DOI: 10.3390/jfmk6040083
|View full text |Cite
|
Sign up to set email alerts
|

Association of Performance in Strength and Plyometric Tests with Change of Direction Performance in Young Female Team-Sport Athletes

Abstract: The change of direction (COD) ability is a task-specific skill dependent on different factors such as the degree of the turn, which has led to differentiating CODs as more force- (>90°) or velocity-oriented (<90°). Considering force and velocity requirements is of importance when designing sport-specific training programs for enhancing COD performance. Thus, 25 female handball and soccer players participated in this study, which investigated the association between three different strength and plyometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Accordingly, there could exist a transfer between the strength training program and the force-oriented COD manoeuvre as earlier research has found both bilateral and quarter squat performance to be associated with force-oriented COD performance in a similar population [ 23 ]. It is not possible to evaluate the isolated effect of the different exercises, but it could be speculated that the bilateral back squat shares similarities with the pivot in the force-oriented COD.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Accordingly, there could exist a transfer between the strength training program and the force-oriented COD manoeuvre as earlier research has found both bilateral and quarter squat performance to be associated with force-oriented COD performance in a similar population [ 23 ]. It is not possible to evaluate the isolated effect of the different exercises, but it could be speculated that the bilateral back squat shares similarities with the pivot in the force-oriented COD.…”
Section: Discussionmentioning
confidence: 99%
“…Three tests were utilized to measure strength by external load lifted (bilateral, lateral, and unilateral squat), as well as three plyometric tests: drop-jump (reactive strength index), skate-jump length, and unilateral countermovement jump height. The different tests were retrieved from earlier research in which such tests were thoroughly described [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations